The Effect of Concentrated Ownership on Tax Avoidance: CSR Mediates or Moderates - Kinanti, Syahfira Putri; Midiastuty, Pratana Puspa; Suranta, Eddy; Putra, Danang Adi (Ilomata International Journal of Tax and Accounting, 2024)
This study seeks to empirically demonstrate the relationship between concentrated ownership and tax avoidance, exploring the potential role of Corporate Social Responsibility (CSR) as either a mediating or moderating variable. From the aim of this research, the formulation of the problem in this research is whether concentrated ownership has an effect on tax avoidance and this research wants to further prove whether CSR is more appropriate to use as a mediating or moderating variable in explaining the relationship between concentrated ownership and tax avoidance. The research focuses on a selection of manufacturing firms that uphold CSR values during the period from 2019 to 2021, employing purposive sampling as the method for sample selection. Concentrated ownership is defined as ownership exceeding 50%, while tax avoidance is measured using the Effective Tax Rate (ETR). The results prove that concentrated ownership encourages management to conduct tax avoidance as an effort to obtain additional capital for the firm's investment needs so that companies tend to shift current taxes to future taxes. This research proves the existence of agency problems where concentrated ownership expropriates minority interests. CSR functions as a moderating factor in the correlation between concentrated ownership and tax avoidance. It serves to diminish managerial endeavors in evading taxes by establishing corporate legitimacy. With better implementation of CSR, it is hoped that this will not be a motivation for companies to avoid taxes when companies are dominated by concentrated ownership and investors prefer to invest in companies that have concentrated shares.